Kesenjangan Gender (Perempuan) dalam Mendapatkan Pendidikan pada Masyarakat Pedesaan - Sri Maharani; Khairina Tambunan (Universitas Muhammadiyah Enrekang, 2022)
Education is one of the fundamental construction of the transformation process that plays an important role in the development movement. But in fact, education in Indonesia today still shows a low quality and uneven. Education gap is still felt by the gender in Blitar, East Java Tugurejo village. This research uses qualitative research methods with instruments in the form of an open interview (interview guide) with a data source that is data Primary and Secondary Data with purposive sampling technique. Observation data collection and interviews with a systematic analysis of the data in accordance with data obtained from interviews, observation, and documentation. The results of the study explained that the education gap female (gender) in the village of Tugurejo really happened, namely the notion that education is more important for men than for women. Factors causing the education gap, namely; economic factors, cultural, environmental, socially, mindset, as well as educational facilities are minimal. The impact of public education is low which affects the development of the village, both physical and non-physical and the development of society itself.